Edukasi Bertani Di Kecamatan Mandastana Sebagai Mitigasi La-Nina Di Bidang Pertanian - Indriani; Masliyana; Abdillah, Muhammad Helmy; Lukmana, Mila; Rahmawati, Linda; Ishwahyudi, Herry; Nur, Raybian; Prasetya, Yosef Lucy Dwi (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
Rainfall variability has become the biggest challenge in increasing crop yields. Statistical data shows that a decrease of 20% in harvested area and 27% in rice production in Barito Kuala Regency from 2020 to 2023 has a fatal impact on the exchange rate of rice in the market. This is partly due to changes in the duration of the dry season and rainy season due to El-Nino and La-Nina as well as tropical cyclones that occur in Indonesia. The impact is that some coastal and lowland areas will continue to be inundated for a long period as a result of which harvest area and land productivity will decrease. Therefore, education about farming on flood-prone land must be disseminated to increase farmer resilience and encourage farmers to continue using their land even in flood conditions. This activity aims to disseminate knowledge and applicable technology to increase the productivity of rice fields as a weather mitigation effort. The hope is that participants will accept and implement the farming methods presented in this extension. The results show that the material on rice cultivation technology using the floating method, techniques for biological disease control in rice, and weather forecasting for planning agricultural activities can be understood and participants are interested in implementing them as resilience in flood conditions